Analisis Implementasi Kurikulum Merdeka Pada Mata Pelajaran PAI Perspektif Teori Belajar Konstruktivisme dan Humanisme di SMA N 2 Purwokerto - Muhammad Alifian Ferdi Ikhsan; Hanif, Muhammad (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This study aims to analyze the implementation of Merdeka Curriculum in Islamic Religious Education (PAI) subjects at SMA N 2 Purwokerto, from the perspective of constructivism and humanism learning theories. The research method used is qualitative, with data collection techniques through classroom observation, interviews with teachers and students, and document analysis. The results showed that the implementation of Merdeka Curriculum in PAI subjects at SMA N 2 Purwokerto is still in its early stages. Teachers began to apply several constructivistic and humanistic learning principles, such as project-based learning, problem-based learning, and cooperative learning. However, there are still some obstacles faced, such as the teacher's lack of understanding of constructivistic and humanistic theories, limited learning resources, and lack of support from the school. The results of this study indicate that the implementation of Merdeka Curriculum in PAI subjects at SMA N 2 Purwokerto still needs to be strengthened. Teachers need to improve their understanding of constructivistic and humanistic theories, and get better support from the school to implement learner-centered learning.